Perancangan Sistem Informasi Inventory Barang Berbasis Web untuk Menggantikan Pencatatan Manual pada Toko Ayra Plafon PVC dengan Metode Waterfall - Dimas Anugrah Pratama; Muhammad Riffaldy Satriatama; Mushaffah M. Azizi Rifky; Maulana Ardhiansyah (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
The utilization of information systems in business activities plays an important role in improving the effectiveness, efficiency, and accuracy of inventory data management. Based on observations conducted at AYRA Plafon PVC, the inventory management process was still performed manually using stock record books, resulting in several operational problems such as discrepancies between physical stock and recorded data, delays in data retrieval, and difficulties in preparing inventory reports. This study aims to design and develop a web-based inventory information system to overcome these issues. The system was developed using the Waterfall methodology, with PHP Native as the programming language and MySQL as the database management system. The resulting system provides integrated features for managing product data, customer data, stock-in transactions, stock-out transactions, stock opname, and inventory reporting. System testing was conducted using the Black Box Testing method, and the results indicate that all system functionalities operate correctly according to user requirements. Therefore, the developed system is capable of improving the effectiveness and efficiency of inventory management at AYRA Plafon PVC.